2022
DOI: 10.53730/ijhs.v6ns9.12245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the otago exercise program on the lower extremity muscle strength in older women

Abstract: An increased risk of falls in the elderly is associated with decreased muscle mass and strength in the lower limbs. The Otago Exercise Regimen (OEP) is a moderately challenging walking, flexibility, strengthening, and balancing exercise regimen. The Otago Exercise Program has been demonstrated to reduce the incidence of falls in elderly individuals by improving balance and muscular strength. This research sought to ascertain how the Otago Exercise Program influenced the lower limb muscular strength of older wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…The small effects resulted from exercise is likely because of the short period of intervention as only two weeks, that inadequately obtain positive outcome in function. Previous study showed significant improvement in FTSST in longer periods after 6 weeks and 12 weeks of aerobic and core stability exercise [12] while TUG after 8 and 12 weeks of exercise treatment [39,40]. This is supported by a study investigated responsiveness of TUG to minimal change that could be detected in 2 weeks after multidiscipline treatment in frail patient supports the result of the current study [41][42][43][44].…”
Section: Resultssupporting
confidence: 85%
“…The small effects resulted from exercise is likely because of the short period of intervention as only two weeks, that inadequately obtain positive outcome in function. Previous study showed significant improvement in FTSST in longer periods after 6 weeks and 12 weeks of aerobic and core stability exercise [12] while TUG after 8 and 12 weeks of exercise treatment [39,40]. This is supported by a study investigated responsiveness of TUG to minimal change that could be detected in 2 weeks after multidiscipline treatment in frail patient supports the result of the current study [41][42][43][44].…”
Section: Resultssupporting
confidence: 85%
“…Specifically, these exercises focus on strengthening the quadriceps, hamstrings, hip abductors, calf muscles, and tibialis anterior muscles [14]. In line with our findings, OEP have been found to reduce the incidence of falls in elderly individuals by improving balance and muscular strength [11]. There was a significant correlation between group and time, suggesting that the OEP can assist in improving muscle strength (p < .05) [15].…”
Section: Discussionsupporting
confidence: 79%
“…Participants were encouraged to select a weight, allowing them to perform eight to ten repetitions before experiencing muscle fatigue. It's important to note that this fatigue threshold may vary for each exercise and each leg [11].…”
Section: The Oep For Group (A)mentioning
confidence: 99%